Role of astrocytes and glutamate transporter EAAT2 / GLT1 in Amyotrophic Lateral Sclerosis - Daniel Castro; Elke Díaz; Irma Lombardo; Patricia Cassina; Laura Martínez-Palma (Anales de la Facultad de Medicina, 2017)
Amyotrophic Lateral Sclerosis (ALS) is a fatal, progressive neurodegenerative disease affecting upper and lower motor neurons of the central nervous system that is associated to  glial reactivity. The pathogenesis of this disease is not entirely clear. Different mechanisms have been postulated, including alterations in RNA processing, protein metabolism, axonal transport and mitochondrial function, increased oxidative stress and excitotoxicity. Astrocytes exhibit processes surrounding the synapse, where glutamate transporters are located to uptake the excess of neurotransmitter during synaptic activity. Alterations in this mechanism have been found in ALS and have highlighted the role of glia in the progression of ALS. Glutamate acts on two receptor families: NMDA and non-NMDA. There is evidence that links glutamate transporters dysfunction to the pathogenesis of the disease. In addition, it has been proven that alteration in the function and availability of the glutamate transporter EAAT2 / GLT1contributes to the increase of extracellular glutamate concentration. In this work, we aim to review the literature on the role of astrocytes and the glutamate transporter EAAT2 / GLT1 in the pathogenesis of ALS, to identify unsolved questions that may guide further research to improve the treatment of these patients.